Abstracts of the 15th Congress of the African Association of Nephrology (Mombasa, 25-28 September 2019) - Soki, Khalida (African Journal of Nephrology, 2020)
Abstracts of the joint AFRAN and AFPNA Congress, hosted by the Kenya Renal Association, held in Mombasa, Kenya, 25-28 September 2019. Abstracts published as received.